Environmental Kuznets Curve Model for the United States: A Consideration of Foreign Direct Investment Variable - Bunnag, Tanattrin (International Journal of Energy Economics and Policy, 2023)
This paper analyzes the causal link between CO2 emission, energy consumption, GDP, the square of GDP, and foreign direct investment in the Environmental Kuznets Curve for the United States from 1979-2021. Three steps are used: bound tests to verify the presence of cointegration, autoregressive distributed lag (ARDL) model to check the effects of the dependent variables on the independent variable in the short run and long run, and finally, the vector error correction (VECM) was used the detect the causal relationships among variables. We found that the coefficients of energy consumption and foreign direct investments variables were significant at the 10% level. The variables GDP and GDP2 were found to be insignificant. Energy consumption positively impacts CO2 emissions, while FDI negatively influences CO2 emissions. In addition, in causal analysis, it is found that GDP and GDP2 indirectly affect CO2 emissions. GDP and GDP2 impact energy consumption and FDI; later, FDI was passed through CO2 emission. Finally, the federal government should accelerate investment policies, tax credits, regulatory actions, state policies, research and development, and market trends to drive significant renewable deployment.